The Implementation of Polluter Pays Principle in Indonesian Land Policy Regulation - Melly Aida; Ikhsan Setiawan (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2021)
Many lands are degraded; they are no longer productive, vital, damaged, or utilized and are instead overgrown with shrubs. The majority of the causes of this land degradation are irresponsible and arbitrary human actions. What is more perplexing is that these actors are not immediately punished for their actions but are instead allowed to roam freely outside. As a result, this research will discuss the accountability of land destroyers, which is based on one of the principles of international law, namely the “Polluter Pays Principle,” which requires an actor who is a land destroyer to be held accountable for all of his actions in an amount equal to the impact on the land itself. The application of the Polluter Pays Principle is hoped to improve the control and maintenance of land policy in Indonesia.